IDENTIFIKASI KERUSAKAN VEGETASI HUTAN MANGROVE DI DESA SUNGAI BAKAU KALIMANTAN SELATAN - Susilawati, Susilawati; Asy'ari, Mufidah; Pujawati, Eny Dwi; Salsabila, Shania (Universitas Lambung Mangkurat, 2024)
The purpose of this study was to identify the type of damage to mangrove forest vegetation in Sungai Bakau Village. The object of this research is Mangrove forest vegetation in Sungai Bakau Village. Primary data is obtained through field observations by observing each individual mangrove forest vegetation at the pole and tree level in the observation plot. The primary data is then processed and described each type of damage. The results obtained from research on the identification of mangrove forest vegetation health are the types of damage found in this study in the form of fungal fruiting bodies, open wounds, gumosis, broken stems / roots, brooms on roots, stems or branches, loss of shoots or dead shoots, broken or dead, damage to leaves or shoots and discoloration of leaves.